SMARTPHONE DISTRACTIONS IN VOCABULARY LEARNING AMONG UNIVERSITY STUDENTS - Agustiani, Aulia; Triana Ramdha; Nurul Masyithah Rery; Sri Nurussima Awani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The pervasive use of smartphones in Indonesia has significantly impacted educational practices, offering substantial benefits for vocabulary learning, such as easy access to information and interactive applications. However, these devices also present a major challenge: digital distraction. This study investigates the types and contributing factors of distractions experienced by second-semester English students at a university in Indonesia during vocabulary learning via smartphones. Data were collected through a questionnaire administered to 33 students and follow-up interviews with three selected respondents. Quantitative findings revealed that notifications or pop-up messages (75.8%), texting (72.75%), social media and entertainment applications (68.2%), and multitasking (68.15%) were the most prevalent and disruptive types of distractions. Qualitative analysis further contextualized these distractions, highlighting habitual app-switching and the allure of entertainment content as key disruptors. The factors contributing to these distractions were identified as low self-regulation (74.7%), attentional impulsiveness (69.6%), and the ease of access to social media (71.7%). Interview data underscored the role of emotional regulation, such as using entertainment apps to combat boredom or tiredness, and habitual behavior in exacerbating these distractions. The study concludes that while smartphones are powerful tools for language learning, their potential for distraction is significant and multifaceted. It recommends that students adopt better self-regulation strategies and use focus-enhancing features, while educators and institutions should integrate digital literacy training to promote more mindful and effective smartphone use in academic contexts.